2006
DOI: 10.1021/jp062427j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Route to WOx Nanorods and WS2 Nanotubes from WS2 Inorganic Fullerenes

Abstract: WO(x) (2 < x < 3) and WS(2) nanostructures have been widely praised due to applications as catalysts, solid lubricants, field emitters, and optical components. Many methods have been developed to fabricate these nanomaterials; however, most attention was focused on the same dimensional transformation from WO(x) nanoparticles or nanorods to WS(2) nanoparticles or nanotubes. In a solid-vapor reaction, by simply controlling the quantity of water vapor and reaction temperature, we have realized the transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
3
19
0
2
Order By: Relevance
“…for their spray deposited nano crystalline WO 3 thin films. The blue emission at 418 nm [34,37,38] and blue green emission at 488 nm [38,39] were also close to the reported results. The blue green and blue emission peaks were more intense than the near UV emission and this kind of emissions were already reported [35].…”
Section: Photoluminescence Studiessupporting
confidence: 87%
“…for their spray deposited nano crystalline WO 3 thin films. The blue emission at 418 nm [34,37,38] and blue green emission at 488 nm [38,39] were also close to the reported results. The blue green and blue emission peaks were more intense than the near UV emission and this kind of emissions were already reported [35].…”
Section: Photoluminescence Studiessupporting
confidence: 87%
“…In our work, the blue emission peak locals at 420 nm (2.60 eV) which is in accordance with the WO 3 energy gap of 2.4-2.8 eV. But the wavelength measured in this work is shorter than that reported [2,8] , which may be due to the size-effect of the nano-materials. Figure 5 shows the PL property of the nanotubes, the big unsymmetrical tail is observed, and the existence of emission peak at long wavelength maybe originates from the presence of oxygen vacancies defects or K impurity.…”
Section: Photoluminescence Propertiessupporting
confidence: 89%
“…Li et al [8] studied the PL properties of WO 3 nanorods, and found the emission peak at 438 nm. In our work, the blue emission peak locals at 420 nm (2.60 eV) which is in accordance with the WO 3 energy gap of 2.4-2.8 eV.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…Among various metal oxide semiconductors, tungsten oxide (WO 3−x ), which is a wide band-gap n-type semiconductor, has been considered as a promising sensing material for detection of toxic gases [11,12]. Recent studies about onedimensional tungsten oxide nanostructures like W 18 O 49 nanowires and WO 3 nanotubes have clearly demonstrated the good prospects of tungsten oxide nanostructures in toxic and hazardous gas detection [13][14][15].…”
Section: Introductionmentioning
confidence: 99%